2013
DOI: 10.1002/uog.11200
|View full text |Cite
|
Sign up to set email alerts
|

Automated three‐dimensional coded contrast imaging hysterosalpingo‐contrast sonography: feasibility in office tubal patency testing

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 23 publications
1
43
0
1
Order By: Relevance
“…One study using 2D-HyCoSy as reference standard was excluded because a 2 × 2 table could not be constructed [8]. Therefore, 9 studies were ultimately included in this systematic review [13,14,15,16,17,18,19,20,21]. No additional studies were found from references cited in the papers included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…One study using 2D-HyCoSy as reference standard was excluded because a 2 × 2 table could not be constructed [8]. Therefore, 9 studies were ultimately included in this systematic review [13,14,15,16,17,18,19,20,21]. No additional studies were found from references cited in the papers included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…7 Compared with 2D HyCoSy, 3D HyCoSy requires less time, 36 avoids difficult probe movements and is less dependent on operator skill. 4,7,37 Automated 3D volume acquisition of the entire fallopian tube easily shows the course of the tube and image acquisition also permits storage and later analyses of captures. 7,38 However, because the 3D HyCoSy is a static imaging method, it cannot display the real-time process of contrast agent flow in fallopian tubes.…”
Section: Subgroup Analyses and Publication Biasmentioning
confidence: 99%
“…5 But, the cost of both the new machine and contrast medium is considerable in clinical practice. 37 This study systematically assessed the diagnostic accuracy of 3D/ 4D HyCoSy for detecting tubal patency in females suffering from infertility. No strong heterogeneity between studies and publication bias was observed.…”
Section: Subgroup Analyses and Publication Biasmentioning
confidence: 99%
“…A cheap but highly operator-dependent reported alternative for these products during HyCoSy is to use an alternated injection of water and air in the uterine cavity and to sonographically detect air bubbles around the ovary and free fluid in the cul-de-sac [11,12,13]. More recently, Exacoustos et al [13,14] introduced coded contrast imaging enabling the visualization of the fallopian tubes over their total length. However, coded contrast imaging requires special software and a second-generation contrast medium.…”
Section: Introductionmentioning
confidence: 99%